Determinants of Budget Absorption: The Role of Regulation as Moderator - Nurfadila Rizky Pratiwi; Perwito Perwito; Jeri Sukmawijaya (Yayasan Riset dan Pengembangan Intelektual, 2023)
In the wheel of government, one measure of the success of a government is how to utilize a budget that will have an impact on economic growth and public welfare. A low level of budget absorption will lead to budget inequality which leads to inefficiency in budget allocation. This study aims to explore the determinants of budget absorption which include budget planning, and budget implementation, and aims to assess the extent of the role of regulation in moderating the effect of budget planning and budget implementation on budget absorption. The research population is the West Java Regional Secretariat Law and Human Rights Bureau employees. The study used a quantitative descriptive method with hypothesis testing using SPSS software. The research findings prove that budget planning has a positive effect and budget implementation has a negative effect on budget absorption. Meanwhile, the findings of this study indicate that regulation does not provide a moderating effect on the relationship but in budget implementation, the regulation provides a moderating effect. The research implies the importance of knowing the aspects of budget absorption so that the budget provided can be absorbed optimally and effectively for the public interest.